DOMNIEMANIE OJCOSTWA - RATIO DECIDENDI USTAWODAWCY - Jurewicz, Aldona (Zeszyty Prawnicze, 2017)
Paternity’s presumption - ratio decidendi of Legislator Summary Paternity’s presumption is an important legal tool in contemporary Polish civil law. It enables e.g to define the civil status of a private person. Paternity’s presumption is regulated in art 62 §1 i 85 § 1 of k.r.o. Undoubtedly we cannot reduce its effect to the sphere of legal proceedings and the authorconsiders, that the intention of the legislator was different. The legislator found it necessary to regulate the child’s origin by a legal presumption, which allows to establish legal connections between the child and the husband or partner of the child’s mother. Some scholars claim, that the ancient Roman law knew the paternity’s presumption. There is a probable confirmation - a passage from Paul’s Edict Commentary, which was placed by compilers in D. 2,4,5: Quia [mater] semper certa esty etiam si vulgo conceperit: pater vero is est> quaem nuptiae demonstrant This kind of a presumption in Roman law was applied only in order to establish the child’ s origins and it’s legal status on the grounds of iustum matrimonium. Nevertheless analysis of the problem allows a theory, that a presumption was applied not only in the issues connected with providing evidence. The aim of this article is to answer questions concerning some common points in ratio decidendi of ancient Roman legislator and the contemporary Polish one. In the author’s opinion, the similarity lies in an attempt to protect basic values against an excessive interference of law into individual life.